Effect of oral contraceptives on weight and body composition in young female runners - Procter-Gray, E.; Cobbs, K. L.; Crawford, S. L.; Bachrach, L. K.; Chirra, A.; Sowers, M.; Greendale, G. A.; Nieves, J. W.; Kent, K.; Kelsey, J. L. (Medicine & Science in Sports & Exercise, 2008)
Purpose: To examine the effect of oral contraceptives (OC) on body weight, fat mass, percent body fat, and lean mass in young female distance runners.